2013
DOI: 10.3724/sp.j.1141.2012.02119
|View full text |Cite
|
Sign up to set email alerts
|

Cranial morphometric study of four giant flying squirrels (<I>Petaurista</I>) (Rodentia: Sciuridae) from China

Abstract: Abstract:The present study revisited the controversial taxonomic status of Petaurista yunanensis, P. philippensis, P. hainana, and P. petaurista by using a considerably extended set of morphometrical characters (26 cranial variables from 60 adult specimen skulls). The results revealed no sexual dimorphism in any of the four species but confirmed significant craniometric differences among the four species in both the principal components analysis (PCA) and discriminant function analysis (DFA), with the greatest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…In most of the parts measured, specimens from Ado-Ekiti tends to stand out when compared with the remaining locations (Ile-Ife, Sekona and Emure-Ekiti). This is similar to the report of Li, et al [24] reported craniometric differences among the four species of giant flying squirrels in China. For further confirmation of the differences, F. leucogenys specimens collected from all the locations were pooled and subjected to PCA to determine whether the recorded variations were significant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In most of the parts measured, specimens from Ado-Ekiti tends to stand out when compared with the remaining locations (Ile-Ife, Sekona and Emure-Ekiti). This is similar to the report of Li, et al [24] reported craniometric differences among the four species of giant flying squirrels in China. For further confirmation of the differences, F. leucogenys specimens collected from all the locations were pooled and subjected to PCA to determine whether the recorded variations were significant.…”
Section: Discussionsupporting
confidence: 92%
“…All these cranial characters showed the discrimination among the locations. This was also similar to the report of, Li et al [24] on the cranial measurement of giant flying squirrels in China. The differences observed may be attributed to the urbanization of the location where specimens in Ado-Ekiti was collected which influence the type of life style tree squirrels were living.…”
Section: Multivariate Analyses Of the Craniometrics Datasupporting
confidence: 92%
“…The differences were likely affected by the adaptation of C. notatus in Sangir that lived in an area large arbor plant as well as being near to the secondary forest whereas C. notatus populations founded in Lubuk Basung and Baso were located at the plantation area with palm trees and cacao. Li et al (2012) stated that the phenotype divergence may have regard to the geographical distribution and living conditions, and can serve as a reflection of the adaptation form of the different ecological niches. Hansson and Henttonen (1988) reported that the populations of the same species in different habitats could indicate variations due to the influence of extrinsic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric studies of intra-specific or inter-specific variations by quantitative analysis are valuable for detecting patterns of geographic variations and delimiting intra-specific or inter-specific evolutionary units Li et al (2012). Hale and Luz (2003) revealed that there are morphological changes in British red squirrel (Sciurus vulgaris) as a result of introduced species and changes in landscape management.…”
Section: Introductionmentioning
confidence: 99%